O discurso constituinte como determinante no uso de tópoi e argumentos retóricos na construção das epístolas de Sêneca e Paulo - Santos, Zilda Andrade Lourenço dos (2017)
This research was elaborated from the construction of a parallel between the production of the epistles of Seneca and Paul, during the first century of our era. The constituent discourse is the determining element in the way of conducting the trajectory of the epistolary genre. Seneca is guided by the paths of philosophical discourse, while Paul supports his text based on religious discourse. As a starting point, one counts on the support of Foucault in his investigations on the writing of itself like an ingredient in the prescription of the care of itself, in the Antiquity. It is noted that epistolography plays a fundamental role in that historical moment, functioning not only as a means of communication between the sender and recipient, but a form of exposition of the subjectivity that is revealed by the acquisition of the true discourses. These discourses are manifested in the individual's way of acting, determining the discursive position occupied by the ethos in the enunciation. The assumptions of discourse analysis, with an enunciative basis, in Maingueneau's approach and other researchers, in this same line, provide theoretical support for the analyzes. In the generic scene of the enunciation occurs the construction of the discourse genre and this requires a discursive scenography that directs it in the enunciative act, revealing the ethos of the enunciator, responsible for the discourse. The epistle as genre, in the writings of Seneca and Paul, provides space for each one to develop their arguments according to the basic foundations of ancient rhetoric. Starting from the constituent discourses, philosophical and religious, these authors resort to certain topoi, commonplace, and rhetorical arguments that are developed in the construction of their epistles. At the frontiers of philosophical, literary and religious discourses are the influences of Hellenistic culture that contributes to the approximation of these constituent discourses, exerting an effect of intercrossing, causing the interdiscourse phenomenon. Thus, the discursive positions of Seneca and Paul sometimes come closer together and sometimes departing, in view of the constituent discourses that direct them.